Vehicle entry-exit ramp basement plan and section (RFA-144_Rev I) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture (BUCG-ABC JV); Web Structures (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF & DWG version of drawings.